Investigating the Relationship between Socioeconomic Factors and Incidence of Leukemia - Soraya Nouraei Motlagh; Parvaneh Heidari Orojlo; Farhad Lotfi; Marita Mohammadshahi; Nasrin Shaarbafchi Zadeh (Tehran University of Medical Sciences, 2016)
Background and Aim: Cancer disease is one of the main problems of Iranian health system. It is after Cardiovascular diseases and accidents, the third leading cause of death in Iran. In many countries, differences in socio-economic status have been linked with the incidence of disease, death and in general, health inequalities. The aim of this study is to determine the socioeconomic factors associated with the incidence of leukemia in Iran. Materials and Methods: The present descriptive-analytical study was done with panel data modeling, including information related to 30 provinces of Iran from 2004 to 2009. Socioeconomic data were collected from provincial statistical yearbooks and data on age-standardized incidence rate (ASIR) of leukemia cancer per 100,000 populations were obtained from published reports by Iran Cancer Registry.  Results: The results showed that the leukemia incidence in men and in women during the period under review has been upward. The highest and lowest incidence of leukemia was in Yazd and Sistan provinces, respectively. Direct relationship between unemployment rate, urbanization ratio, and human development index with cancer incidence rate was evident in this study. Conclusion: The increase of leukemia cancer in Iran has been confirmed by the current study. Leukemia cancer was significantly higher among provinces with higher socioeconomic status. This should be considered for planning support.